Transformation of social and political demands through ballot box: from los Indignados to Podemos - Bedir, Nurdan Selay (Middle East Technical University, 2017)
After 2008 crisis, alternative remedies and resistance against this age’s predominant neoliberal policies have been sought in many states and societies. Europeans harshly encountered with the crisis and governments’ and the EU’s crisis management policies raised multilateral and multilevel struggles like: the Pots and Pans Revolution in Iceland (2009), the Geração à Rasca in Portugal (2011), the Indignant Citizens Movement in Greece (2010), and los Indignados (15M) in Spain (2011). These movements had worldwide repercussions. Spain’s struggle fueled the emergence of a political party, differently from others. Several academic studies have been performed on the Spanish movement and the party (Podemos) established in the aftermath of the movement from various perspectives. This thesis focuses on the tensions arising from the transformation of social and political demands of the los Indignados movement into the institutional politics. The study addresses to movement’s and party’s populist characters, impact of economic crisis on lives of Spanish people, inextricability of politics and economics, politicization and strengthening of economic demands, their reflections on elections, and liberal democracy. Accordingly, an analysis within the context of institutionalization of los Indignados movement and its demands by a political party, Podemos, has been conducted on the basis of the tensions. In consequence, the thesis argues that despite the tensions, which Podemos is at the center and criticisms raised against Podemos, it is the main denominator of the new political stage in Spain opened by los Indignados and its existence and attitude within the Spanish and European politics should not be disregarded because of its potential for future struggles. M.S. - Master of Science